PERSUASIVE STRATEGIES OF SHOES SELLER IN “TAFT” INSTAGRAM ACCOUNT - Christian Jourdan Tambunan; I Wy Dirgeyasa (Universitas Negeri Medan, 2022)
This research was deals with the Persuasive Strategies of Shoes Seller in TAFT instagram account. The objective of the research were to discover the types of persuasive techniques of shoes seller in TAFT Instagram account, and to describe the strategies used by shoes seller on TAFT Instagram account. This study was conducted by using qualitative method. The data in this research were collected by using documentary technique. There were 84 written captions selected consecutively from November 2019 to January 2020. The findings found that there were only six from seven types of persuasive technique were used in TAFT written captions such as rationalization (23 posts), identification (7 posts), suggestion (40 posts), conformity (3 posts), compensation (6 posts), and projection (5 posts). And the strategy of persuasion that was used in TAFT’s Instagram account were Logos, Phatos, and Ethos. Mostly, the user uses the logical reason (Logos) with 52.38% percentage.Keywords: Persuasive, Shoes Seller, Instagram, TAFT